2023
DOI: 10.3390/antibiotics12030494
|View full text |Cite
|
Sign up to set email alerts
|

Infections in Glucose-6-Phosphate Dehydrogenase G6PD-Deficient Patients; Predictors for Infection-Related Mortalities and Treatment Outcomes

Abstract: Disturbances in the count or maturity of blood cells weaken their microbial defensive capacity and render them more susceptible to infections. Glucose-6-phosphate deficient patients are affected by a genetic disease that affects cell integrity with increased liability to infections and death. We aimed to investigate the risk factors for infection mortality in this patient population. We retrospectively examined the records of G6PD adult patients with confirmed infections and collected data related to demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…This finding is in line with the association between ADHD and inflammatory somatic conditions [36][37][38], between ADHD and infectious diseases [25][26][27] and between G6PD deficiency and COVID-19 infection and immune-related diseases [39]. G6PD-deficient patients, similar to individuals with ADHD, exhibit a higher incidence of infectious diseases worldwide, indicating a vulnerability to infections [40,41]. Exposure to infectious conditions and certain foods or medicines among G6PD-deficient subjects affect RBCs, leading to hemolysis associated with neurological and psychiatric problems.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This finding is in line with the association between ADHD and inflammatory somatic conditions [36][37][38], between ADHD and infectious diseases [25][26][27] and between G6PD deficiency and COVID-19 infection and immune-related diseases [39]. G6PD-deficient patients, similar to individuals with ADHD, exhibit a higher incidence of infectious diseases worldwide, indicating a vulnerability to infections [40,41]. Exposure to infectious conditions and certain foods or medicines among G6PD-deficient subjects affect RBCs, leading to hemolysis associated with neurological and psychiatric problems.…”
Section: Discussionsupporting
confidence: 76%
“…Studies have demonstrated that individuals with ADHD exhibited higher rates of infections including COVID-19 [25,26] with higher rates of severity [29,47] and complications [27]. Similarly, it was shown that G6PD-deficient individuals have a higher incidence of infectious diseases, indicating a predisposition to infections [40,41,45,46,48]. Our previous study showed that G6PD-deficient individuals had a higher risk of COVID-19 infection, of COVID-19 hospitalization, and of developing long-COVID [46].…”
Section: Discussionmentioning
confidence: 94%